First record of a natural hybrid of the genus Gongora (Stanhopeinae) and comments on the parent species - Jiménez-Vázquez, Alexander (2023)
The first natural hybrid of the genus Gongora is described for the department of Copán in Honduras, between the species Gongora truncata and Gongora batemanii (synonym: Gongora cassidea). The nothospecies described here presents intermediate characteristics between both species, such as setaceous projections on the lip, a large callus, spatulate epichile, and a cucullate hard dorsal sepal. The identity of a specimen from the Herbarium Jany Renz Botanical Institute, University of Basel, Switzerland, corresponds to the same hybrid described here and erroneously determined as Gongora saccata, a synonym of Gongora seideliana, is considered. The clarification of the synonymy of Gongora saccata and relevant aspects regarding the pollination mechanisms and reproductive barriers of both parent species are also discussed.